MEMPROGRAMKAN PENGENALAN BANK SYARIAH PADA DESA CIBITUNG KULON, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Thantawi, Tubagus Rifqy; Anwar, Miftakhul; Mumtazah , Naura Tanzilia (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2024)
This community service activity discusses the introduction of Sharia Banking to the people of Desa Cibitung Kulon, Kecamatan Pamijahan, Kabupaten Bogor. The aim of this community service activity is to provide an introduction to sharia banking to the people of Desa Cibitung Kulon with the hope that the people in this village can understand the existence of sharia banking which is now everywhere, both in villages and urban areas. The community service method used in this community service is the participatory transparency method. The result of this community service activity is that it can provide knowledge and insight to the people of Desa Cibitung Kulon, Kecamatan Pamijahan, Kabupaten Bogor about Sharia Banking in detail.